Epidemiology of Traumatic Brain Injury After Small-Wheeled Vehicle Trauma in Utah. Issue 6 (December 2015) - Majercik, Sarah; Day, Suzanne; Stevens, Mark H.; MacDonald, Joel D.; Bledsoe, Joseph
Abstract : BACKGROUND: Recreational use of small-wheeled vehicles (SWVs), which include skateboards, longboards, nonmotorized scooters, ice skates, and roller skates or rollerblades, results in numerous injuries in the United States. OBJECTIVE: To describe the nature and severity of traumatic brain injuries (TBIs) that result from the use of SWVs in Utah. METHODS: Patients who were admitted to any Utah hospital after a SWV-related injury from 2001 through 2010 were identified from the Utah State Trauma Registry. Patients who sustained TBI were identified by International Classification of Diseases, Ninth Revision, codes. RESULTS: Of 907 patients admitted with SWV injury, 392 (43%) had a TBI (85% male). Their mean age was 19.8 ± 0.5 years, including 234 (60%) aged ⩽18 and 119 (30%) aged 19 to 29. Most patients sustained TBI while using a skate- or longboard (87%). Mean Glasgow Coma Scale score in the emergency department was 12.8 ± 0.2. Thirty-nine percent were admitted to an intensive care unit, and 6% (23) underwent emergent neurosurgical intervention. Thirty-three (8.4%) patients had a concussion; the rest had nonoperative intracranial hemorrhage. Among patients for whom helmet use data were available, 8 out of 291 (2.7%) patients with TBI were wearing a helmet, whereas 24 out of 190 (12.6%) non-TBI patients were wearing helmets ( P < .001). Overall mortality was higher in TBI patients than in non-TBI patients (2.3% vs 0.2%, P = .003). CONCLUSION: Young people, especially males, who ride SWVs in Utah are at risk for serious TBI, admission to the intensive care unit, neurosurgical intervention, and death. Helmet use in these patients is likely rare, but may reduce the risk of TBI and death. ABBREVIATIONS: ED, emergency department SWV, small-wheeled vehicle TBI, traumatic brain injury